Targeting HOX-PBX interactions causes death in oral potentially malignant and squamous carcinoma cells but not normal oral keratinocytes - Platais, Christopher; Radhakrishnan, Raghu; Niklander Ebensperger, Sven; Morgan, Richard; Lambert, Daniel W.; Hunter, Keith D. (BMC cancer, 2018)
High HOX gene expression has been described in many cancers, including oral squamous cell carcinoma and the functional roles of these genes are gradually being understood. The pattern of overexpression suggests that inhibition may be useful therapeutically. Inhibition of HOX protein binding to PBX cofactors by the use of synthetic peptides, such as HXR9, results in apoptosis in multiple cancers. Activity of the HOX-PBX inhibiting peptide HXR9 was tested in immortalised normal oral (NOK), potentially-malignant (PMOL) and squamous cell carcinoma (OSCC) cells, compared to the inactive peptide CXR9. Cytotoxicity was assessed by LDH assay. Expression of PBX1/2 and c-Fos was assessed by qPCR and western blotting. Apoptosis was assessed by Annexin-V assay. PMOL and OSCC cells expressed PBX1/2. HOX-PBX inhibition by HXR9 caused death of PMOL and OSCC cells, but not NOKs. HXR9 treatment resulted in apoptosis and increased expression of c-Fos in some cells, whereas CXR9 did not. A correlation was observed between HOX expression and resistance to HXR9. Inhibition of HOX-PBX interactions causes selective apoptosis of OSCC/PMOL, indicating selective toxicity that may be useful clinically.